(untitled) (Global Journals of Research in Engineering, 2012)
This paper introduce the design and development of multifunctional sensor nodes, the design based on microcontroller which represent the heart of any low cost R.T.U. A small size R.T.U can be used as a server provides the required data in the remote area. The proposed R.T.U is of low cost, low power, easy to implement and efficient to be used in different applications.